Pengaruh Tingkat Pengungkapan Sukarela Dalam Laporan Tahunan Terhadap Koefisien Respon Laba - Sovi Ismawati Rahayu (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The objectives of the research is to find out the impact of luntaty disclosures on earnings response coefficient (ERC). The populati n of this study was public manufacturing companies listed at Jakarta Stoc Exchange in 2005 period. There were 31 manufacturing companies meet th criteria was chosen as sample. This research is explanatory research, and th data analysis were treated as cross-section. Earning persistence, systematic risk company growth, leverage and company size which in prior stOies described ERC variation, in this research used as controlling vaable. The research hypothesis were tested using the multiple regression analysis. The result ofthis research before and after use the which described ERC variation show that voluntary disclosure had significantly negative influence on earnings response coefficientKeywords: Voluntary Disclosures, Earnings Response Coeficient